2018
DOI: 10.1016/j.geomphys.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Lie symmetries for systems of evolution equations

Abstract: The Lie symmetries for a class of systems of evolution equations are studied. The evolution equations are defined in a bimetric space with two Riemannian metrics corresponding to the space of the independent and dependent variables of the differential equations. The exact relation of the Lie symmetries with the collineations of the bimetric space is determined.Lie symmetries is a powerful method for the determination of solutions in the theory of differential equations. A Lie symmetry is important as it provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
2
4
0
1
Order By: Relevance
“…In [19], [20] it has been shown that in these case the Lie point symmetries are generated by the special projective algebra and the Noether point symmetries by the Homothetic algebra of the kinetic metric. Similar results have been found for some partial differential equations of special interest in curved spacetimes, as the wave and the heat equation (see [21], [22], [23] and references therein) where it has been shown that in these cases the Lie point symmetries involve the CKVs.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…In [19], [20] it has been shown that in these case the Lie point symmetries are generated by the special projective algebra and the Noether point symmetries by the Homothetic algebra of the kinetic metric. Similar results have been found for some partial differential equations of special interest in curved spacetimes, as the wave and the heat equation (see [21], [22], [23] and references therein) where it has been shown that in these cases the Lie point symmetries involve the CKVs.…”
Section: Introductionsupporting
confidence: 80%
“…We conclude that the Bianchi III spacetime A + λ which reduces to a HV when A (τ ) is an exponential in which case the line element is ds 2 (III) = −e mκτ dτ 2 + e mκτ dx 2 + e m(κ−1)τ dy 2 + e m(κ−λ)τ e −2x dz 2 (23) or in equivalent form…”
Section: Ckvs Of Bianchi III Spacetimementioning
confidence: 88%
See 1 more Smart Citation
“…Lie symmetry method provides an effective tool for deriving the analytic solutions of the nonlinear partial differential equations (NLPDEs) [1][2][3][4]. In recent years, many authors have studied the nonlinear fractional differential equations (NLFDEs) because these equations express many nonlinear physical phenomena and dynamic forms in physics, electrochemistry, and viscoelasticity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ωστόσο, δεν υπάρχει ένα τέτοιο ισχυρό αποτέλεσμα για την περίπτωση των δυναμικών συμμετριών (Lie και Noether). ΄Εχουν εξαχθεί, παρόμοια αποτελέσματα, για την περίπτωση των μερικών διαφορικών εξισώσεων δεύτερης τάξης, [185][186][187][188] καθώς και για την περίπτωση διαταραγμένων συναρτήσεων Lagrange, βλέπε [189]. Ακόμα, αποτελέσματα που να αφορούν συναρτήσεις Lagrange που παρουσιάζουν ανωμαλία (singular Lagrangians), οι οποίες αφορούν συστήματα με δεσμούς μπορούν να βρεθούν στα [190,191].…”
Section: εισαγωγήunclassified